2018
DOI: 10.3892/or.2018.6198
|View full text |Cite
|
Sign up to set email alerts
|

Combination of gemcitabine and erlotinib inhibits recurrent pancreatic cancer growth in mice via the JAK-STAT pathway

Abstract: Compared to single gemcitabine treatment, the combination of gemcitabine and erlotinib has shown effective response in patients with locally advanced or metastatic pancreatic cancer. However, the combination therapy has not proven effective in patients with pancreatic cancer after R0 or R1 resection. In the present study, a nude mice model of orthotopic xenotransplantation after tumor resection was established using pancreatic cancer cell lines, BxPC-3 and PANC-1. Mice were divided in four groups (each with n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“… 69 , 70 Similar anti-tumor drugs in PC target the JAK-STAT pathway and may have a potential application in chemotherapy and immunotherapy. 71 , 72 Therefore, we can hypothesize that these prognostic miRNAs are involved in biological processes and signaling pathways by regulating their target genes and affecting PC tumorigenesis and treatment. Regarding the top five significant target genes, the present study is the first to identify a significant association between these mRNA expression levels and PDAC OS.…”
Section: Discussionmentioning
confidence: 99%
“… 69 , 70 Similar anti-tumor drugs in PC target the JAK-STAT pathway and may have a potential application in chemotherapy and immunotherapy. 71 , 72 Therefore, we can hypothesize that these prognostic miRNAs are involved in biological processes and signaling pathways by regulating their target genes and affecting PC tumorigenesis and treatment. Regarding the top five significant target genes, the present study is the first to identify a significant association between these mRNA expression levels and PDAC OS.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact mechanism of this pathway’s cachectic effect is unclear, it is likely due to an increase in pro-inflammatory cytokines, acute phase reactants, and catabolic factors. Intracellular JAK2-STAT3 pathway is activated by weight loss and inflammation associated cytokines IL-6, IL-11, leukaemia inhibitory factor, and TNF-α; thus inhibition is both multi-faceted and approachable[33,40,41]. Multiple studies have demonstrated attenuation of cachexia by inhibiting the JAK2-STAT3 pathway or its downstream signaling colorectal and lung cancer[36-39].…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…For the last 2 decades, Gem has become the reliable drug regimen for advanced PC, as it has shown significant betterment in the median overall survival of patients in clinical trials (Sinn et al, 2017;Goess and Friess, 2018). Large bodies of research evidence suggest the advantages of using combination therapy of Gem with other cytotoxic agents (Von Hoff et al, 2013;Hamada et al, 2017;Chakraborty et al, 2018;Chen et al, 2018). Although these combination therapies show significant improvement in prolongation of overall median survival in clinical trials, long-term survival of patients remains poor (American Cancer Society, 2017), demanding novel effective therapeutic approaches against disease progression.…”
Section: Discussionmentioning
confidence: 99%